Anthropological Perspective on Gender Disparities in India - Delliswararao, Konduru (International Journal of Social Sciences and Management, 2021)
Gender is a social term; it is using for both male and female. But due to the inequality and discrimination, the gender term is more adopted only to female or women discrimination. In developing countries like India, gender inequality, discrimination is very high due to so many factors, such as economical factors, cultural factors and others. India is 140th Rank, out of 156 countries in world's gender gap index. It is showing that India's performance in gender equality. Not only a govt, every individual in the society are responsible for the gender inequality in India. When comparing with other nations, India’s ranking is lower than African countries. The main objective of the present paper explains the socio-cultural, economical, and other factors in various sectors in Pondicherry related to gender equality. Another aim of the study is to understanding the women development in a holistic manner. The methodology of the paper is Mixed Method of research. Int. J. Soc. Sc. Manage. Vol. 8, Issue-3: 416-425.